Diversity of dermal fibroblasts as major determinant of variability in cell reprogramming. Issue 6 (13th April 2019) - Sacco, Anna Maria; Belviso, Immacolata; Romano, Veronica; Carfora, Antonia; Schonauer, Fabrizio; Nurzynska, Daria; Montagnani, Stefania; Di Meglio, Franca; Castaldo, Clotilde
Abstract: Induced pluripotent stem cells (iPSCs) are adult somatic cells genetically reprogrammed to an embryonic stem cell‐like state. Notwithstanding their autologous origin and their potential to differentiate towards cells of all three germ layers, iPSC reprogramming is still affected by low efficiency. As dermal fibroblast is the most used human cell for reprogramming, we hypothesize that the variability in reprogramming is, at least partially, because of the skin fibroblasts used. Human dermal fibroblasts harvested from five different anatomical sites (neck, breast, arm, abdomen and thigh) were cultured and their morphology, proliferation, apoptotic rate, ability to migrate, expression of mesenchymal or epithelial markers, differentiation potential and production of growth factors were evaluated in vitro. Additionally, gene expression analysis was performed by real‐time PCR including genes typically expressed by mesenchymal cells. Finally, fibroblasts isolated from different anatomic sites were reprogrammed to iPSCs by integration‐free method. Intriguingly, while the morphology of fibroblasts derived from different anatomic sites differed only slightly, other features, known to affect cell reprogramming, varied greatly and in accordance with anatomic site of origin. Accordingly, difference also emerged in fibroblasts readiness to respond to reprogramming and ability to form colonies. Therefore, as fibroblasts derived from different anatomic sites preserve positional memory, it is of great importance to accurately evaluate and select dermal fibroblast population prior to induce reprogramming.